2013
DOI: 10.1111/j.1600-0587.2013.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Are protected areas maintaining bird diversity?

Abstract: Evaluating the effectiveness of protected areas for sustaining biodiversity is crucial to achieving conservation outcomes. While studies of effectiveness have improved our understanding of protected‐area design and management, few investigations (< 5%) have quantified the ecological performance of reserves for conserving species. Here, we present an empirical evaluation of protected‐area effectiveness using long‐term measures of a vulnerable assemblage of species. We compare forest and woodland bird diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 42 publications
3
39
0
Order By: Relevance
“…It has since been reduced, but conversion of wooded habitat in the wet tropics bioregion is still estimated at approximately 423 hectares per annum, although the rate of conversion is lower within protected areas (DERM, 2010), indicating that they may be important future refuges. Our findings are supported by recent work on woodland birds in New South Wales, Australia, which indicates protected area effectiveness for vulnerable woodland birds is strongly influenced by the physical characteristics and landscape context of the site, and can diminish with changes in surrounding land use over time (Rayner et al, 2013).…”
Section: Management Implicationssupporting
confidence: 83%
See 1 more Smart Citation
“…It has since been reduced, but conversion of wooded habitat in the wet tropics bioregion is still estimated at approximately 423 hectares per annum, although the rate of conversion is lower within protected areas (DERM, 2010), indicating that they may be important future refuges. Our findings are supported by recent work on woodland birds in New South Wales, Australia, which indicates protected area effectiveness for vulnerable woodland birds is strongly influenced by the physical characteristics and landscape context of the site, and can diminish with changes in surrounding land use over time (Rayner et al, 2013).…”
Section: Management Implicationssupporting
confidence: 83%
“…However, even when protected areas are successful in maintaining species populations, gap analysis based on biodiversity hotspots and threatened species coverage has concluded that protected areas alone are not adequate for nature conservation in the long term (Rodrigues et al, 2004;Virkkala & Rajas€ arkk€ a, 2007;Watson et al, 2010). Both protected areas and off-reserve conservation schemes have important roles to play in securing species populations (Rayner et al, 2013), and the actions of the WTMA and local landholders in the face of these challenges will therefore be vital for ongoing maintenance of rain forest avifauna.…”
Section: Management Implicationsmentioning
confidence: 99%
“…, Rayner et al . ). Protection, including national park status and other designations, does not always provide strict protection to either parrots or the forest in which they live (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Establishing PAs could be effective in directly reducing human impacts within targeted forests, but in many instances might be driven more by markets than by conservation or ecological considerations (Rayner et al . ). Many PAs lack additionality because they are situated in locations passively protected by their distance to markets, unproductive soils, steep gradients, etc.…”
Section: Examples Of Conservation Measures and Market Feedbacksmentioning
confidence: 97%